2022
DOI: 10.1002/hep4.1927
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and outcomes of subsequent therapy after immune checkpoint inhibitor discontinuation in HCC

Abstract: The availability of immune checkpoint inhibitors (ICIs) for the management of advanced hepatocellular cancer (HCC) has changed the treatment paradigm. There are emerging questions regarding the efficacy of subsequent anticancer therapies. The primary aim of this retrospective, multicenter study was to examine the types of anticancer treatment received after ICIs and to assess the impact on post‐ICI survival. We established an international consortium of 11 tertiary‐care referral centers located in the USA (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In general, patients may receive other ICIs based on different mechanisms, such as programmed cell death-1 ( PD-1 ) versus programmed death-ligand 1 (PD-L1) or based on the treatment course (nivolumab for the pembrolizumab group or pembrolizumab for the nivolumab group). Increasing evidence has demonstrated a re-challenge of immunotherapy in the management of HCC [ 33 , 34 ]. Schenier et al demonstrated that the ORR was approximately 22%, with a median time to progression of 5.2 months, indicating that ICI rechallenge was relatively safe and contributed to a treatment benefit in a meaningful proportion of patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients may receive other ICIs based on different mechanisms, such as programmed cell death-1 ( PD-1 ) versus programmed death-ligand 1 (PD-L1) or based on the treatment course (nivolumab for the pembrolizumab group or pembrolizumab for the nivolumab group). Increasing evidence has demonstrated a re-challenge of immunotherapy in the management of HCC [ 33 , 34 ]. Schenier et al demonstrated that the ORR was approximately 22%, with a median time to progression of 5.2 months, indicating that ICI rechallenge was relatively safe and contributed to a treatment benefit in a meaningful proportion of patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor control is difficult with these therapies alone; therefore, in real-world practice, sequential therapy using various MTAs and ICIs, without impairing liver reserves, aims to prolong PFS and OS [ 8 , 16 ]. A recent retrospective study regarding outcomes of subsequent therapy after ICI discontinuation, it was shown that receipt of post-ICI therapy including MTAs was associated with longer median OS compared with those who had received the best supportive care (12.1 vs. 3.3 months; hazard ratio: 0.4; 95% confidence index: 2.7–5.0) [ 17 ]. Another study shows that in patients with advanced HCC after progressive disease on atezolizumab plus bevacizumab, the median PFS of second-line treatment with lenvatinib was significantly longer than that of sorafenib (6.1 vs. 2.5 months; p = 0.004) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Talbot et al [ 14 ] reported that the post-progression survival of HCC patients treated by both continuation of ICI and switching to TKIs after failure of ICI-based therapy was significantly longer than that of patients with only best supportive care (10.3 vs. 1.9 months, p < 0.0001). Sharma et al [ 15 ] analyzed patterns and outcomes of subsequent therapy after ICI discontinuation in 420 HCC patients and showed that patients receiving post-ICI therapy were associated with longer median OS compared with those who had received best supportive care (12.1 vs. 3.3 months; HR: 0.4, p < 0.001). Although these studies are somewhat limited by their retrospective approach, these global multicenter trials support the use of ICI in the second-line setting in patients with good liver functional reserve and ECOG performance status.…”
Section: Second-line Treatment Versus Best Supportive Carementioning
confidence: 99%